Comparative outcomes of unilateral biportal endoscopic lumbar intervertebral discectomy with and without annulus fibrosus suture in lumbar disc herniation: a retrospective analysis - Zhou, Wei; Bangura, Mohamed Lamin; Gong, Qianlong; Zhang, Rong; Zeng, Teng; Fei, Qi; Chirima, Tadiwa Chiedza; Tran, Sy-Trung; Qiu, Yutian; Luo, Huasong (Frontiers in Surgery, 2025)
BackgroundAdvancements in minimally invasive spine surgery have markedly enhanced patient outcomes in the management of lumbar intervertebral disc herniation and degenerative disorders. The Unilateral Biportal Endoscopic Interlaminar Lumbar Intervertebral Discectomy and spinal nerve decompression are prominent of these methods. This method is based on the principles established by several endoscopic spine techniques, which are lauded for their limited invasiveness, less trauma, and expedited recovery periods in contrast to conventional open operations.Methods177 patients treated with Unilateral Biportal Endoscopic Transforaminal Lumbar Intervertebral Discectomy for lumbar disc herniation were selected and assigned into Sutured (39 patients) and Un-sutured groups (138 patients). Different variables, including clinical outcomes and estimated cost, were evaluated using IBM SPSS 27.0.1 with a p-value < 0.05 considered statistically significant.ResultsThe study identified disparities in clinical outcomes, such as reoperation problems, surgery durations, and projected costs between the two groups. Reoperation rates were lower in the sutured group. Un-sutured patients had a shorter surgery time. Both groups had comparable Visual Analog Scale (VAS) and Japanese Orthopaedic Association (JOA) scores. Both groups have similar Body Mass Indexes (BMIs) throughout hospitalization. The two groups had equal discharge satisfaction scores. There is not much variation in surgical bleeding across groups. Follow-up times were identical for both groups (26.46 ± 2.01 for the sutured group and 26.83 ± 2.68 for the un-sutured group). The two groups showed a slight difference in estimated costs, with the sutured group averaging RMB 29,234.78 ± 5,265.83, compared to RMB 22,311.10 ± 3,527.00 for the un-sutured group.ConclusionAnnulus fibrosus suturing during minimally invasive lumbar disc surgery may increase time and expense and reduce the risk of recurrent herniation and reoperation. Sutured and non-sutured techniques have equal clinical results and low intraoperative blood loss, making them feasible alternatives depending on the situation and patient demands.